MENELUSURI TRADISI LISAN PARNO (PANGKU PARBAYO) ADAT DESA KOTO MAJIDIN, KABUPATEN KERINCI SEBAGAI WUJUD IDENTITAS MASYARAKAT - Ravico Ravico (Fakultas Adab dan Humaniora UIN Raden Fatah, 2019)
Introduction: This article discusses the oral tradition of the people of Koto Majidin village, namely parno adat Data Cellection Method: The stages in oral tradition research include literature studies and observation. Analysis Data: To trace the traditional parno tradition of Koto Majidin Village, qualitative research was used with a descriptive method, namely trying to describe and explain traditional customs so that they could know the substance of the parno. Furthermore, this study uses a cultural theme analysis. Results and Dicussions: Oral tradition is a tradition that has been passed down from one generation to the next. With the progress of the development of human life and the development of science, the oral tradition has been eliminated from people's lives. In the lives of urban people, this oral tradition has begun to disappear. But the existence of this oral tradition can still be found in rural areas. One of them is in Koto Majidin Village, Kab. Kerinci, namely the parno adat oral tradition. Parno adat whose existence still exists in traditional community celebrations, if not reviewed. So it is feared that there will be extinction. Conclusion: This analysis is used to conduct culture-oriented research by looking for red threads that are related associated with values, ethos, and culture. The results of this study, if viewed from the values contained in the customary community of Koto Majidin Village are religious, agrarian and humanist societies. Furthermore, the values of the traditional parno wisdom of Koto Majidin Village relate to ideological values and advice.